2020
DOI: 10.1038/s41598-020-60635-w
|View full text |Cite
|
Sign up to set email alerts
|

MBW complexes impinge on anthocyanidin reductase gene regulation for proanthocyanidin biosynthesis in persimmon fruit

Abstract: MBW protein complexes containing MYB, bHLH and WD40 repeat factors are known transcriptional regulators of secondary metabolites production such as proanthocyanidins and anthocyanins, and developmental processes such as trichome formation in many plant species. DkMYB2 and DkMYB4 (MYB-type), DkMYC1 (bHLH-type) and DkWDR1 (WD40-type) factors have been proposed by different authors to take part of persimmon MBW complexes for proanthocyanidin accumulation in immature fruit, leading to its characteristic astringent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The astringency, being a distinctive characteristic of Chaenomeles fruit taste, is present due to the high content of proanthocyanidins (TPCC). According to the literature, the amount of TPCC in fruit may vary depending on the maturity, agricultural practices as well species (Gil‐Muñoz et al., 2020; Yu et al., 2020). The research available so far indicates that the amount of TPCC in JQ fruit varies from 4.0 to 6.3 g/kg (Miao et al., 2016; Watychowicz et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The astringency, being a distinctive characteristic of Chaenomeles fruit taste, is present due to the high content of proanthocyanidins (TPCC). According to the literature, the amount of TPCC in fruit may vary depending on the maturity, agricultural practices as well species (Gil‐Muñoz et al., 2020; Yu et al., 2020). The research available so far indicates that the amount of TPCC in JQ fruit varies from 4.0 to 6.3 g/kg (Miao et al., 2016; Watychowicz et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several transcription factors crucial for PA accumulation in persimmon have been identified as DkMYB2/4 , DkMYC1, and DkWDR1 as homologs of TT2 , TT8, and TTG1 , respectively ( Akagi et al, 2009b ; Akagi et al, 2010a ; Naval et al, 2016 ). In yeast and Nicotiana benthamiana, it has been shown that DkMYB2, Shalini, and DkWDR1 interact together to act as a MBW-complex ( Gil-Muñoz et al, 2020 ). Moreover, in PCNA fruits, Dk MYB4 regulates the expression of ANR and F3′5′H ( Akagi et al, 2009b ).…”
Section: Proanthocyanidins or Condensed Tanninsmentioning
confidence: 99%
“…It is the polymers of flavan-3-ols and the resultant product of flavonoid pathway [81]. PA is the most extensively spread secondary metabolites and is mainly prominent in forest trees and woody plants [82]. In trees, proanthocyanidins are general constituents of vegetative parts which consist of flowers, leaves, bark, seed and roots [83], and provide protection to plants from various abiotic and biotic stressors.…”
Section: The Role Of Condensed Tannins In Plants and Mybmentioning
confidence: 99%